2021
DOI: 10.1002/jemt.24020
|View full text |Cite
|
Sign up to set email alerts
|

Structure and distribution of antennal sensilla in Pseudosymmachia flavescens (Brenske) (Coleoptera: Scarabaeidae: Melolonthinae)

Abstract: Morphology, microstructure, and distribution of antennal sensilla were compared between female and male Pseudosymmachia flavescens (Brenske) (Coleoptera: Scarabaeidae: Melolonthinae). Lamellate antennae of P. flavescens were shown to have typical scape, pedicel, and flagellum segments. The flagellum consists of a four‐segmented funicle and a three‐segmented club. The lengths of their pedicel and funicle were found to be similar in females and males. Distinct sexual differences were observed in the length of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…This differential odour sensitivity could potentially be attributed to the differential distribution of olfactory receptors responding to chemical cues. As an example, the middle lamella of the scarab beetle Pseudosymmachia flavescens (Coleoptera: Scarabaeidae: Melolonthinae) generated higher EAG responses than those of the proximal or distal lamella and the closed antennal club, which was found to have a significant correlation with the density of sensilla placodea in a previous study [27,62]. Single sensillum recordings (SSRs) have shown that olfactory neurons housed in densely arranged sensilla basiconica in G. auratus were sensitive to indole, skatole, phenol and p-cresol, while a separate group of olfactory cells responded specifically to butanone [28,48].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This differential odour sensitivity could potentially be attributed to the differential distribution of olfactory receptors responding to chemical cues. As an example, the middle lamella of the scarab beetle Pseudosymmachia flavescens (Coleoptera: Scarabaeidae: Melolonthinae) generated higher EAG responses than those of the proximal or distal lamella and the closed antennal club, which was found to have a significant correlation with the density of sensilla placodea in a previous study [27,62]. Single sensillum recordings (SSRs) have shown that olfactory neurons housed in densely arranged sensilla basiconica in G. auratus were sensitive to indole, skatole, phenol and p-cresol, while a separate group of olfactory cells responded specifically to butanone [28,48].…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, sensilla type, density and distribution on antennae may impact the sensitivity profile for odorant molecules. Although the antennal morphology and sensilla structure have been characterised in many coleopteran families, the antennal sensory apparatus of dung beetles is still poorly understood [26,27]. Only a few studies have investigated the morphology and distribution of antennal sensilla in dung beetles, specifically Geotrupes auratus, Copris pecuarius [28], Typhaeus typhous, Onthophagus fracticornis and Aphodius fossor [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paprides nitidus antennae are also shorter and have signi cantly smaller segments than those of S. australis.In many grasshopper species males have more sensilla on their antennae than females (80% of 75 species examined byBland 1989, Chen et al 2003and Li et al 2007). These sexual differences are attributed to sexual selection on males to have high sensitivity to pheromones released by females(Chen et al 2003;Malo et al 2004;Wee et al 2016;Li et al 2021b). As the New Zealand alpine grasshoppers tend to be visually cryptic (to avoid visual predators) and do not generate acoustic signals with wings when searching for mates…”
mentioning
confidence: 99%